Cytokine correlations in childhood-onset rheumatic diseases with pulmonary involvement - Huang, Hua; Ding, Fei; Liu, Chenxi; Bao, Shengfang; Jin, Yingying; Jin, Yanliang; Bao, Yixiao (Frontiers in Pediatrics, 2024)
Background: There was less research about cytokines in lung involvement of childhood-onset rheumatic diseases (RD) patients. Objective: In this investigation, blood levels of 12 cytokines were tested in order to explore their associations with lung involvement in newly diagnosed childhood-onset RD patients . Methods: High-resolution computed tomography (HRCT) and pulmonary function tests (PFTs) were performed on 53 newly diagnosed RD patients without any treatment in our department between July 2021 and December 2023. Patients were separated into groups based on whether their lungs were involved or not according to abnormalities found on HRCT or PFTs. We examined the serum cytokines with 41 healthy, age and gender-matched controls. Results: The majority of serum cytokine levels were statistically different between the RD group with lung involvement and the control group. The RD group with lung involvement had considerably higher serum IL-6 and IFN-γ levels than the RD group without lung involvement or control group. The median serum IL-6 levels were 19 pg/ml (interquartile range [IQR] 6.9, 27.6), 4.4 pg/ml (IQR 2.0, 10.5), and 2.0 pg/ml (IQR 2.0, 2.0) in RD group with lung involvement, RD group without lung involvement, and control group, respectively. Similarly, the median serum IFN-γ levels were 6.0 pg/ml (IQR 5.0, 15), 5.0 pg/ml (IQR 5.0, 5.0), and 5.0 pg/ml (IQR 5.0, 5.0) in RD group with lung involvement, RD group without lung involvement, and control group, respectively. The receiver operating characteristic (ROC) curve study showed that IL-6 and IFN-γ had area under the curve (AUC) values of 0.782 and 0.742, respectively, indicating their significant diagnostic potential for lung involvement in RD patients. Conclusion: Our findings imply that IL-6 and IFN-γ may be associated with the development of lung illnesses and may be involved in the pathophysiology of RD. Thus, in individuals with RD, elevated levels of IFN-γ over 5.42 pg/ml or IL-6 above 6.25 pg/ml may warrant suspicion of lung involvement.